2020
DOI: 10.1186/s13244-020-00922-2
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-derived myocardial extracellular volume: an early biomarker of cardiotoxicity in esophageal cancer patients undergoing radiation therapy

Abstract: Objectives We aimed to assess extracellular volume (ECV) through non-gated, contrast-enhanced computed tomography (CT) before and after radiation therapy (RT) in patients with esophageal cancer (EC). Materials and methods EC patients who had undergone CT before and after RT were retrospectively assessed. Patients with preexisting cardiovascular disease or with heavily artifacted CT were excluded. ECV was calculated using density values for the myocardial septum and blood pool. Data were reported as mean and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Although our data on non-CTRCD patients are consistent with those reported in the literature, to our knowledge we are the first to show data in CTRCD patients, reporting at baseline a range of mECV values (PP = 26.9–30 % and DP = 26–28.7 %) similar to previous observations [ 24 , 35 , 36 ]. Although our patients are younger (median 45 ± 4 years) than those described in other studies reported so far [ 24 , 26 , 36 ], the role of AD in reducing cardiac contractility and increasing the risk of CTRCD was already described [ 10 , 13 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although our data on non-CTRCD patients are consistent with those reported in the literature, to our knowledge we are the first to show data in CTRCD patients, reporting at baseline a range of mECV values (PP = 26.9–30 % and DP = 26–28.7 %) similar to previous observations [ 24 , 35 , 36 ]. Although our patients are younger (median 45 ± 4 years) than those described in other studies reported so far [ 24 , 26 , 36 ], the role of AD in reducing cardiac contractility and increasing the risk of CTRCD was already described [ 10 , 13 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although our data on non-CTRCD patients are consistent with those reported in the literature, to our knowledge we are the first to show data in CTRCD patients, reporting at baseline a range of mECV values (PP = 26.9–30 % and DP = 26–28.7 %) similar to previous observations [ 24 , 35 , 36 ]. Although our patients are younger (median 45 ± 4 years) than those described in other studies reported so far [ 24 , 26 , 36 ], the role of AD in reducing cardiac contractility and increasing the risk of CTRCD was already described [ 10 , 13 , 37 , 38 ]. In a similar study on patients treated with AC, a cumulative cardiotoxicity incidence of 1.2 % per year was observed in patients younger than 55 years, reaching a 10.6 % risk in patients over-75 years [ 39 ], thus suggesting a synergy between drug cardiotoxicities and AD.…”
Section: Discussionsupporting
confidence: 91%
“…Lastly, it is critical to note that the ECV in our study was measured using thoracic contrast-enhanced CT, including cardiac images, rather than specific cardiac CT. However, a study has confirmed the possibility of contrast-enhanced CT in measuring left ventricular ECV ( 29 ). In our study, images were acquired from portal phase, and the principle of images acquisition from portal phase has been addressed in various articles ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…CT-derived ECV has shown strong correlations to MRI-derived ECV [47]; thus, findings related to the role of ECV in monitoring cancer therapy-related cardiotoxicity may potentially translate from MRI to CT, and the two modalities could also be used interchangeably according to clinical needs. For instance, previous studies have shown that myocardial ECV, assessed at non-gated contrast-enhanced CT, rises significantly in breast cancer patients undergoing anthracycline-based regimens [48] and in patients with esophagus cancer treated with chest radiotherapy [49]. In this sense, while it might not be realistic to screen each patient undergoing cancer treatment for cardiotoxicity using MRI, MRI could be reserved to high-risk patients, such as those with previous comorbidities, undergoing therapies such as anthracyclines or radiation therapy, which are known to yield a dose-dependent effect [50].…”
Section: Discussionmentioning
confidence: 99%